Aumento da resistência à corrosão por refusão a laser do aço 316L - Cruz, Ana Larissa Soares (Universidade Federal de São Carlos, 2024)
Austenitic stainless steels (ASS), notably AISI 316L, are recognized for their combination of high mechanical strength, toughness, and corrosion resistance in various applications. However, the presence of manganese sulfide (MnS) in AISI 316L stands out as the main cause of pitting corrosion susceptibility. Since electrochemical corrosion is a surface-initiated process, LASER surface remelting (LSR) can be a quick and effective method for eliminating these inclusions, given the process characteristics: high energy density and high heating and cooling rates. This study aims to recover AISI 316L steel compromised by MnS using LSR. The conditions as received and after laser remelting with different energy densities were microstructurally characterized by scanning electron microscopy, transmission electron microscopy, and X-ray diffraction. Additionally, the degree of sensitization (ISO 12732) and chloride-induced corrosion resistance were evaluated, the latter investigated by cyclic potentiodynamic polarization, electrochemical impedance spectroscopy, and inductively coupled plasma mass spectrometry in 0.6 M NaCl solution. XPS analyses were conducted for further characterization of the generated films. Power levels of 150 W and 300 W at an energy density of 2000 J/cm² were found to effectively modify and solubilize coarse and acicular MnS inclusions, resulting in a refined and homogeneous microstructure. The remelted samples exhibit a thick and uniform passive layer rich in Cr₂O₃, with high resistivity values (ρδ), indicating superior electrochemical performance. The results highlight the synergistic effects of higher energy densities and power levels in restoring surface corrosion resistance, enabling the formation of more protective and uniform passive films.
Enhancement in corrosion resistance by laser remelting of 316L stainless steel
Keywords: Engenharia de superfície; Aços inoxidáveis austeníticos; Corrosão por pite; Refusão a laser; Filme passivo; MnS; Surface engineering; Austenitic stainless steels; Pitting corrosion; Laser surface remelting; Passive film; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA